2018
DOI: 10.7566/jpsj.87.094708
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Observation of Heavy Quasiparticle Formation in the Intermediate Valence Compound EuNi2P2: 31P NMR Study

Abstract: We report 31 P NMR measurements under various magnetic fields up to 7 T for the intermediate valence compound EuNi 2 P 2 , which shows heavy electronic states at low temperatures. In the high-temperature region above 40 K, the Knight shift followed the Curie-Weiss law reflecting localized 4 f states. In addition, the behavior corresponding to the temperature variation of the average valence of Eu was observed in the nuclear spin-lattice relaxation rate 1/T 1 . With the occurrence of the Kondo effect, 1/T 1 was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Recent NMR measurements on EuNi 2 P 2 revealed a strong temperature dependence of the spin-lattice relaxation rate 1/T 1 that cannot be explained assuming a simple combination of Eu 2+ and Eu 3+ states. 12 The enhanced effective charge carrier masses of EuNi 2 P 2 and EuIr 2 Si 2 mentioned above suggest a significant hybridization between 4f and conduction electron states at low T due to Kondo interaction. In fact, the formation of heavy bands resulting from a hybridization between Eu 4f and Ni 3d states has been observed directly in photoemission spectroscopy on EuNi 2 P 2 .…”
Section: A Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recent NMR measurements on EuNi 2 P 2 revealed a strong temperature dependence of the spin-lattice relaxation rate 1/T 1 that cannot be explained assuming a simple combination of Eu 2+ and Eu 3+ states. 12 The enhanced effective charge carrier masses of EuNi 2 P 2 and EuIr 2 Si 2 mentioned above suggest a significant hybridization between 4f and conduction electron states at low T due to Kondo interaction. In fact, the formation of heavy bands resulting from a hybridization between Eu 4f and Ni 3d states has been observed directly in photoemission spectroscopy on EuNi 2 P 2 .…”
Section: A Introductionmentioning
confidence: 93%
“…9,10 Recently, EuNi 2 P 2 and EuIr 2 Si 2 attracted considerable interest due to the question of how this hybridization, which is usually observed in Ce and Yb-based Kondo systems, is related to the fluctuating Eu valence. [11][12][13][14] In fact, some of the low-temperature properties of EuNi 2 P 2 and EuIr 2 Si 2 can be explained in the framework of a simple model for VF materials: the interconfiguration fluctuation model. 15,16 In its simplest form it considers Eu 2+ and Eu 3+ states that are close in energy.…”
Section: A Introductionmentioning
confidence: 99%
“…Recent experimental activities have definitely clarified a rich variety of low-temperature properties of the Eu compounds; one can now encounter exotic antiferromagnetic orders, quantum critical phenomena, heavy fermions (HF), and valence transition or crossover phenomena in several Eu compounds, when controlling the pressure and/or the doping rate [1][2][3][4][5][6][7][8][9]. As a basis to clarify the microscopic origin of such interesting physics of the Eu system, we have introduced the Eu-based impurity Anderson model in a previous paper [10] and have shown that the total singlet ground state is realized in the entire region between the divalent and trivalent Eu ion.…”
Section: Introductionmentioning
confidence: 99%